Determinación de la IGE "Inmunoglobulina Alérgeno específico" y su relación parasitaria en niños de edad escolar de 2 a 12 años que acuden a la consulta externa del Centro Materno Infantil Pedro Carbo en los meses de octubre a diciembre del 2013. - Astudillo Morán, Ana Carolina (2015)
This project aims to determine the incidence of parasites in children of early age and detect what are the factors that allow their appearance within the body thereof, through individual analysis on each of the patients through samples both feces and urine with its own diagnosis and the right medication in the form and the case of parasitosis to present, the investigation determined as a result that the parasites were presented more stool samples in the urine since in the urine alone were presented in a total of 5 girls 60 it is therefore concluded that it is not just a favorably low figure, but also that children are more likely to become infected with parasitic infections which were treated with drug metronidazole and albendazole as the case may turn parents were encouraged and sensitized to lead a proper and balanced diet for proper nutrition much needed at that age.